Consistent declining trends in stroke mortality in Brazil: mission accomplished? - Valéria M. A. Passos; Lenice H. Ishitani; Glaura C. Franco; Gustavo C. Lana; Daisy M. X. Abreu; Maria de Fatima Marinho; Elisabeth B. França (Arquivos de Neuro-Psiquiatria)
ABSTRACT Stroke mortality rates are declining in Brazil, but diferences among regions need to be better investigated. The age-adjusted stroke mortality trends among adults (30-69 years-old) from Brazilian regions were studied between 1996 and 2011. Method Data were analyzed after: 1) reallocation of deaths with non-registered sex or age; 2) redistribution of garbage codes and 3) underreporting correction. A linear regression model with autoregressive errors and a state space model were fitted to the data, aiming the estimation of annual trends at every point in time. Results Although there were high values, a steady decrease of rates was observed. The decreasing trends among all regions were statistically significant, with higher values of decline among the Northeast and Northern regions, where rates were the highest. Conclusion Standardized methodology use is mandatory for correct interpretation of mortality estimates. Although declining, rates are still extremely high and efforts must be made towards prevention of stroke incidence, reduction of case-fatality rates and prevention of sequelae.